2020
DOI: 10.24252/mapan.2018v8n1a12
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Science, Technology, Engineering, and Mathematics (Stem)-Based Mathematics Teaching Materials to Increase Mathematical Connection Ability

Abstract: Abstract:This research is development research that aims to develop mathematics teaching materials related to Science, Technology, Engineering, and Mathematics (STEM). This research uses the stages of Research and Development, including problem and data collection, product design, design validation, product test (practicality test), trial test (pretest and posttest), and final product. The results show that teaching materials are valid, practical, and effective to increase mathematical connection ability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The N-gain value is 0.485 in the moderate category. The similarity of this study with other studies, one of which is research from Niam and Asikin (2020) is that both develop STEM-related teaching materials and get Ngain results in the moderate category. While the difference is that in this study the ability tested in the study is the improvement of students' mathematical literacy skills.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The N-gain value is 0.485 in the moderate category. The similarity of this study with other studies, one of which is research from Niam and Asikin (2020) is that both develop STEM-related teaching materials and get Ngain results in the moderate category. While the difference is that in this study the ability tested in the study is the improvement of students' mathematical literacy skills.…”
Section: Discussionsupporting
confidence: 64%
“…The research shows that the teaching materials are valid, practical, and suitable for use. STEM-based teaching materials, to improve students' mathematical connection skills, have also been studied by Niam and Asikin (2020) by showing positive results, in which the teaching materials are valid, practical, and effective in improving students' mathematical connection skills. Martha et al (2021) who developed teaching materials in the form of STEM-based student worksheet also showed that these teaching materials could improve students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that STEM is close to students' real-life problems, so they experience and have the motivation to develop their new literacy skills (N et al, 2022;Yurnetti et al, 2020). This finding was supported by Niam and Asikin (2020), which state that teaching materials in schools do not contain real-life problems and do not yet link the concepts of science, technology, engineering, and mathematics with more detailed and in-depth discussion. Third, students' new literacy skills were still low.…”
Section: Introductionmentioning
confidence: 93%
“…According to Styasih's research, STEM-based worksheets will strengthen pupils' ties to mathematics. [29]. The four components of STEM must be integrated into the learning process for students to engage in STEM learning, which can motivate them to comprehend and manipulate natural phenomena, use technology, and deduce conclusions from data [30].…”
Section: Figure 2 Learning Outcomes Aspects Of Students' Technologica...mentioning
confidence: 99%